TRADISI MUSLIMAH BERCADAR (Studi Living Hadis Pada Masyarakat Tegal Besar Jember) - irfan yuhadi; Nurul Budi Murtini (Al-Majaalis : Jurnal Dirasat Islamiyah, 2019)
Allah Subhanahu wa Ta’ala makes a woman something beautiful in the eyes of men. One of Satan's temptations for men is a woman's problem. Allah Subhanahu wa Ta'ala also ordered the Muslim women to wear hijab by wearing a veil that could cover their heads and chests. Tegal Besar is a sub-district in the Kaliwates sub-district of Jember, East Java. The formulation of the problem in this study is about: (1) the driving factors and stages that are passed by Muslim women in wearing the veil, (2) the challenges faced and pleasures felt by Muslim women after wearing the veil, (3) hadith and atsar which make Muslim women to use veils. The approach in this study is to use a qualitative approach, with this research model is the study of living hadith. The results of this study indicate that: (1) There are 7 driving factors for Muslim women to veil and there are 6 stages that are passed by Muslim women until they succeed in wearing the veil. (2) There are two challenges faced by Muslim women after wearing the veil, namely: accused of following cults and being criticized by people, but they also feel their own pleasure after they continually wear the veil. (3) There are texts on theorem that make Muslim women use veils, both from the traditions of the Prophet Shallalahu aih alaihi wa Sallam and from atsar from Sahabat and Tabi’in.